Aloe Vera/Collagen Mixture Induces Integrin α1β1 and PECAM-1 Genes Expression in Human Adipose-Derived Stem Cells - Faraz Sigaroodi; Hajar Shafaei; Mohammad Karimipour; Mohammad Amin Dolatkhah; Abbas Delazar (Tabriz University of Medical Sciences, 2019)
Purpose: Natural biomaterials are a key base in tissue engineering, and collagen, as the main content of the extracellular matrix (ECM), is frequently used in tissue engineering. Aloe vera has some therapeutic effects on ulcers, therefore, the use of this natural resource has always been considered for improving collagen function. We aimed to evaluate the effect of Aloe vera/ Collagen blended on cell viability, cell attachment, and angiogenic potential by determining of integrin α1β1 and platelet endothelial cell adhesion molecule (PECAM-1) genes expression in human adipose-derived stem cells (hASCs). Methods: In this study, hASCs after harvesting of adipose tissues from abdominal subcutaneous adipose tissue and isolation, were cultured in four groups of control, collagen gel, Aloe vera gel, and Aloe vera/collagen blended in vitro environment at 24h and then cell viability was assessed by MTT (3-(4,5-dimethylthiazol 2-yl)-2,5-diphenyltetrazolium) assay. Integrin α1β1 and PECAM-1 genes expression were evaluated by real-time RT-PCR. Results: The results of MTT showed that the combination of Aloe vera/collagen was retained the cell viability at the normal range and improved it. In real-time RT-PCR results, integrin α1β1 and PECAM-1 gene expression were increased in the Aloe vera/collagen blended group compared to the control group. Conclusion: For tissue engineering purposes, Aloe vera improves collagen properties in the culture of hASCs by increasing the expression of the integrin α1β1 and PECAM-1 genes.